2017
DOI: 10.1515/cclm-2017-0839
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic and prognostic value of presepsin vs. established biomarkers in critically ill patients with sepsis or systemic inflammatory response syndrome

Abstract: Presepsin did not outperform traditional sepsis biomarkers in diagnosing sepsis from SIRS and in prognostication of mortality in critically ill patients. Presepsin may have a limited adjunct value for both diagnosis and an early risk stratification, performing independently of clinical illness severity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
50
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(54 citation statements)
references
References 45 publications
3
50
0
1
Order By: Relevance
“…This has also been demonstrated in various medical wards outside of the critical care environment [72]. Another study suggested that PCT outperforms presepsin, reporting AUCs of 0.791 and 0.674, respectively [88]. A further point of note from this study is that CRP outperformed both, with a relatively high AUC of 0.903.…”
Section: Adults Icusupporting
confidence: 71%
“…This has also been demonstrated in various medical wards outside of the critical care environment [72]. Another study suggested that PCT outperforms presepsin, reporting AUCs of 0.791 and 0.674, respectively [88]. A further point of note from this study is that CRP outperformed both, with a relatively high AUC of 0.903.…”
Section: Adults Icusupporting
confidence: 71%
“…Sepsis, the main reason for high morbidity and mortality in surgical illness, is characterized by systemic inammatory responses to infection. 1,2 It is a common complication of most clinical conditions, such as severe burns, traumas, and surgeries, and is likely to develop into a multiple organ dysfunction, blood coagulation and even death, resulting from the release of various inammatory mediators. 3,4 In recent years, sepsis morbidity all over the world has increased gradually by more than 25%.…”
Section: Introductionmentioning
confidence: 99%
“…Our study has several limitations. First, the sample size is small, although a small number of patients have been used in similar studies [34]. Further investigation is warranted to…”
mentioning
confidence: 99%